Hubungan Tingkat Pengetahuan Diabetes Mellitus dengan Kualitas Hidup Masyarakat Penderita Diabetes Milletus di Desa Salaman - Vera Aulia Putri; Dyah Wiji Puspita Sari; Muh. Abdurrouf (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Diabetes mellitus is an incurable condition that has a major negative influence on its patients' quality of life.  As a result, it is anticipated that the general public, particularly those who have diabetes and their families, will become more knowledgeable about diabetes management and control.  Patients and their families can choose the best course of action for their condition by gaining more knowledge.  Quality of life will be enhanced by appropriate diabetes mellitus knowledge and health-seeking behaviors. The purpose of this study was to determine the relationship between the level of knowledge about diabetes mellitus and the quality of life of people with diabetes mellitus in Salaman Village. This study was a quantitative study with a correlational approach and a cross-sectional design. The sample consisted of 52 respondents using a purposive sampling technique. Data analysis used Spearman rank. The characteristics of 52 people who experience diabetes mellitus are mostly in the late elderly age (56-65 years), mostly female and mostly with junior high school education, mostly with moderate quality of life, and with sufficient knowledge. There is a relationship between the level of knowledge of diabetes mellitus and the quality of life of people with diabetes mellitus in Salaman Village (0.000). It is hoped that diabetes patients will increase their knowledge about diabetes mellitus by participating in counseling or education held by health workers.